Ronald Searle and the Christmas Carol: between animation design and illustration, a story - Benvenuti, Davide (2022)
The 1843 A Christmas Carol by Charles Dickens is probably one of the most adapted pieces of literature we know of live-action, illustration and animation. Ronald Searle (1920-2011), one of the most influential British cartoonists and illustrators of the 20th Century, approached this subject four times over his long career, bringing his personal style to this important work of literature. Searle’s first contact with animation in 1957 triggered a series of professional encounters that would be the beginning of a new chapter in the artist’s life and the start of Searle’s dive into Dickens’ work. By analyzing the personal correspondence and sketch drawings, now preserved in the Ronald-Searle-Archive at the Wilhelm Busch Museum, Germany, we will document the journey that Searle undertook from 1958 to create: 1) an animated feature film, which was never produced 2) illustrations for a publication, first as a commission for Life magazine in 1960 and then for an actual book in 1961, 3) a series of title cards for the live-action film Scrooge in 1970. We will look at the different approaches that Searle and his collaborators took in adapting the same literature for diverse media, not only from a purely artistic point of view but also from the economic, marketing and production issues that came along with the creation of a commercial movie. It is well known that Ronald Searle had a significant influence on the history of design, illustration, and animation, whereas the latter still has unknown projects and uninvestigated aspects. This paper seeks to address some gaps in the academic literature about the illustrator’s contribution to the field of animation while touching on the different animated adaptations of A Christmas Carol.